MULTI-OBJECTIVE OPTIMIZATION DESIGN OF BACKHOE HYDRAULIC EXCAVATOR WORKING DEVICE BASED ON RESPONSE SURFACE METHODOLOGY - ZHANG XianMeng; LI XiangLong; WANG YouGuo (Jixie qiangdu)
In order to improve the comprehensive performance of backhoe hydraulic excavator, a multi-objective optimization design of backhoe hydraulic excavator working device was carried out on the basis of considering the theoretical digging force, static strength and dynamic performance.The strength analysis and modal analysis of the working device are carried out in ANSYS Workbench. By using the optimal Latin hypercube experimental design and response surface methodology, the approximate model of boom strength, bucket strength, working equipment quality, 1 order modal and 2 order modal is established, and the optimization efficiency is improved. Using NSGA-II algorithm, the multi-objective optimization design of the working device is carried out, and the Pareto solution set is obtained. The optimization results show that the quality of the working device decreases, the dynamic performance is improved, the theoretical digging force is increased, and the overall performance of the working device is improved when the constraint is satisfied.